Evaluation of Stigma Related to Perceived Risk for Coronavirus-19 Transmission Relative to the Other Stigmatized Conditions Opioid Use and Depression - Okobi, Sandra; Bergeria, Cecilia L.; Huhn, Andrew S.; Dunn, Kelly E. (Frontiers in Psychiatry, 2022)
Background: The COVID-19 pandemic was initially characterized by misinformation and fear related to transmission that has been previously shown to produce stigma towards persons perceived to be at risk for transmission. This study evaluated perceptions towards scenarios with variable levels of perceived risk for COVID-19 acquisition, and compared stigma towards COVID-19 to depression and opioid addiction. Methods: Respondents (N=280) from the United States completed a web-based survey six months after pandemic declaration. Questions included demographics and COVID-19 misconceptions, expected response to hypothetical scenarios with variable risk for COVID-19, and the Attribution Questionnaire-9 for COVID-19, depression, and opioid addiction. Results: Participants had several COVID-19 misconceptions, including that opioids increased immunity (63.6%), persons were more susceptible based upon racial/ethnic background (63.2%), and underlying health conditions did not influence risk (58.9%). Respondents were highly likely (64/100) to assume someone coughing had COVID-19 and the majority (93.5%) recommended quarantining persons with recent travel. However the majority of respondents (>70% in all cases) also believed they would not change their COVID-19-related behavior when interacting with persons of different racial, ethnic, and age backgrounds. Finally, persons with COVID-19 engendered greater pity, less fear, less blame, less anger, and more willingness to help from respondents relative to persons with opioid addiction. Conclusions: Stigma ratings towards persons perceived at risk of transmitting COVID-19, collected soon after the onset of the pandemic, showed less evidence of stigma relative to persons with opioid addiction despite pronounced misconceptions regarding COVID-19 risk. Data provide a foundation for additional research in this area.